Variable Speed Control Using Fuzzy-PID Controller for Two-phase Hybrid Stepping Motor in Robotic Grinding - Adnan Jabbar Attiya; Salam Waley Shneen; Basma Abdullah Abbas; Yang Wenyu (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In a robotic grinding process, a light-weight grinder is held by an intelligible robot arm. Material removal is carried out by the rotating grinding tool while the end effector of robot guarantees that the tool follows a programmed path in order to work on complex curved surfaces. Grinding tool is driven by Two-Phase Hybrid Stepping motor derive. This work aims to develop a controller based on fuzzy logic to improve the speed control performance of Two-Phase Hybrid Stepping motor derive in order to achieve a controller that provides grinding with higher quality. The analysis and design of PID-Fuzzy controller to improve the response of the motor speed were studied. This paper simulates six motor speed input conditions. The simullink package of the MATLAB. Comparison between the conventional PID controller and Fuzzy-PID output was done on the basis of the simulation result obtained by MATLAB. The simulation results demonstrate that the designed Fuzzy-PID controller realize a good dynamic behavior of the Two-Phase Hybrid Stepping motor, a perfect speed tracking with less rise and settling time, minimum overshoot, minimum steady state error and give better performance compared to conventional PID controller.